The effect of photobiomodulation on regeneration of crushed inferior alveolar nerve caused by iatrogenic injuries in oral and maxillofacial surgeries: A systematic review - Nezafati Saeed; Ghojazadeh Morteza; Pournami Negar (Elsevier, 2022)
Following oral and maxillofacial (OMF) surgeries, inferior alveolar nerve (IAN) damage is common that can lead to sensory disorders. Of course, most of these injuries (nearly 90%) are transient and heal within eight weeks, but they are considered permanent if they last more than six months (Coulthard and et al., 2014) [1]. As a treatment modality, photobiomodulation includes a variety of laser therapy methods with no side effects and no high technique sensitivity (Gasperini et al., 2014) [2]. The present systematic review examined the effectiveness of laser beams at different time intervals on the recovery of damaged IAN. As a systematic review, Medline (PubMed), Cochrane, Scopus, Embase, and ProQuest databases were searched until October 12, 2020, to select articles based on inclusion and exclusion criteria and evaluate their risks of bias based on the JBI checklist (Cousins et al., 2020) [3]. The tests examined included VAS (visual analog scale) for sensitivity, 2-point discrimination, brush stroke, Semmes Weinstein, pinprick nociception, and thermal discrimination. Finally, 12 articles were included. These studies were examined in terms of the time interval between injury and undertaking treatment in three categories: immediate, less than one year, and over two years. In the VAS test, LLLs alone or in combination with LED lasers can only be effective if used immediately after the injury. Improvements in mechanical sensation are very unlikely, and they occur only if immediate treatment is undertaken. In general, photobiomodulation does not affect improving thermal discrimination.